ANALYSIS OF EDUCATION AND SERVICES ON TAX PAYMENT DECISIONS WITH SOCIAL MEDIA AS AN INTERVENING VARIABLE AT THE LUBUK PAKAM TAX OFFICE - Fitri Heldaliani; Nurafrina Siregar; Erwansyah (RADJA PUBLIKA, 2026)
This study analyzes the effect of tax education and fiscal service quality on tax payment decisions, with social media as an intervening variable, among individual taxpayers in the Lubuk Pakam Tax Office jurisdiction. The background of this research stems from the low score for the statement